Chitosan-induced Synergy for Extended Antimicrobial Potency and Enhanced In Vitro Drug Release of Free Base Ciprofloxacin Nanoplexes - Abioye, Amos; Adekunle, Sanyaolu; Paulina, Dudzinska (Bentham Science Publishers, 2021)
Background: Ciprofloxacin free base is practically insoluble in aqueous medium (0.0011 and 0.09 mg/mL at 25 and 37°C respectively). Its inorganic salt form (ciprofloxacin hydrochloride) is more soluble in water (1.35 mg/mL) however when administered orally, it exhibits decreased solubility in the stomach due to common ion effects. Ciprofloxacin free base was used in this study because of its greater hydrophobicity than its hydrochloride salt, which is required for effective permeability and potent antibacterial activity. Objective: The purpose of this study is to enhance oral solubility and bacterial cell permeability of the free base ciprofloxacin (CPX) using a single step CPX-chitosan (CT) selfassembly to form nanoplexes with organic counterions. It was envisioned that this would allow the delivery of larger amounts of active drug into the microorganisms. Methods: Ciprofloxacin-chitosan nanocomplex (nanoplex) was prepared using low energy electrostatic self-assembly technique previously described. Formation of eutectic nanoplex was confirmed using FTIR, DSC, TGA and SEM. The saturated solubility, in vitro release kinetics and mechanism of drug release were determined using mathematical models. Potency and synergism were determined from the inhibition zones, minimum inhibitory concentration (MIC) and Fractional Inhibitory Concentration (FIC) of the nanoplexes using Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Results: Formation of CPX-CT eutectic adduct polymeric nanoplexes was confirmed with FT-IR and DSC and SEM revealed the conversion of rod-like crystals of CPX (117 μm long) into spherical nanostructures (23-503 nm) dictated by pH, ionic strength and concentration of CT. The solubility of free base CPX increased to a maximum of 32.77 mg/mL compared to 0.0011-0.09 mg/mL reported in literature and dissolution efficiency increased to a maximum of 100% within 72 h. The synergistic effect of CT on antimicrobial activity of CPX was quantified, for the first time, using Fractional Inhibitory Concentration (FIC) of the nanoplexes. FIC was less than 0.5 in both Gram positive (0.031-0.250) and Gram negative (0.036-0.281) microorganisms used in this study, confirming synergistic enhancement of antimicrobial efficacy of CPX. Conclusion: It is evident that the design of drug-polymer nanocomplex formulation provides a platform for the synergistic enhancement of therapeutic potency of antibiotics.
Keywords: Bacteriostatic chitosan; ciprofloxacin nanoplexes; extended potency; Fractional Inhibitory Concentrtion (FIC); in vitro drug release kinetics; ACEDHARS; ACE: Drug Research, Herbal Medicine Development and Regulatory Science